Climate Migration Dilemma; Migration as an Adaptation or Maladaptation Strategy - Roghayeh Samadi (سیاست نامه علم و فناوری, 2022)
The potential migration of millions of people due to adverse impacts of climate change is one of the most important issues for governments and policy makers. In this regard, there are various divergent views in the theoretical approach to climate- induced migration: Some scholars believe that migration indicates a failure to adapt to climate change. On the other hand, other scholars believe that migration can be used as a preventive strategy to deal with climate change. By using descriptive-analytical research method, in this study, we attempt to investigate various divergent views in climate migration theories by focusing on the maximalist and minimalist approaches. In addition, we present different climate adaptation strategies taken by policy makers in order to combat adverse consequence of climate changes in other countries. Finally, we analyze various evidences of climate- related movements in Iran and the policies and strategies has been taken by the government regarding to climate adaptation. In general, considering migration as an adaptation or maladaptation strategies creates many challenges for planners and policy makers, which can be controlled through precise strategies. In this regard, policy makers should apply strategies that strengthen the ability of actors to adapt to adverse impacts of climate change.